Genetic and Physiological Studies of Bacteriophage T5 I. An Expanded Genetic Map of T5 - Hendrickson, Herbert E. (1971)
An expanded genetic map of bacteriophage T5 has been constructed by using a set of amber, rather than temperature-sensitive, mutants that represent 29 cistrons. The map consists of three small groups and one large group of genes; mutants defective in genes that are located in different groups exhibit maximal recombination when crossed with one another. However, it has been possible to establish tentative linkage among these groups by use of a particular mutant that appears to affect recombination. One of the small groups of genes is located in the first-step-transfer or FST segment; the other two small groups represent newly discovered genetic regions. The large group probably includes most or all of the previously published maps of T5. The apparent genetic discontinuities are discussed in relation to certain anatomical and physiological features that are unique to bacteriophage T5.